Knowledge Sharing Patterns among Undergraduate Students in Universiti Teknologi MARA (UiTM) Johor, Malaysia - Suhaila Osman; Muna Sauid; Nurhafizah Azizan (International Journal of Management, Accounting and Economics, 2015)
Due to the technology cultured in today’s world, the learning process has started to change. Student nowadays are persistently required to do some transformation in gaining knowledge. Concerning to this, a considerable Knowledge Management (KM) are important so that students are expected to gain the capability of managing their knowledge and to achieve their superior performance. As the consequence, Knowledge Sharing (KS) process will be subsist, as KS is a part of KM. By implementing KS, students will share their knowledge better with their friends in a diligence ways and platform. Two research objectives were addressed in this research that is to examine how culture affect knowledge sharing among Information Management Undergraduate Students’ in UiTM Johor and to investigate the behaviours of Information Management Undergraduate Students’ in UiTM Johor when sharing their knowledge among colleagues. This study use quantitative method to collect and gather the data in which Probability Sampling that is Unrestricted or Simple Random Sampling are chosen as the Sampling Techniques. The researchers are able to collect 70 percent of the distributed questionnaires. Findings show that knowledge sharing activities does exist in UiTM Johor. This study proposed some changes in attitudes and behaviors, trust and innovation, top management support, strong relationship between academicians and students and lastly, rewards to reinforce knowledge sharing behaviorsas the recommendation to the organization.